Analysis of Empirical Studies on the Effect of IFRS on the Cost of Equity Capital - García Carrillo, Jorge Fernando; Laverde Sarmiento, Miguel Ángel; Lezama Palomin, Juan Carlos (Cuadernos de Contabilidad, 2024)
The objective of the article is to correlate the results of empirical investigations that measure the impact of the adoption of IFRS on the cost of equity from an exploratory qualitative study, whereby means of an information collection matrix, 22 articles from indexed journals were reviewed and the information related to the econometric models, the period of publication and analysis, the effects by region, the variables used, the recommendations and limitations of the research. Therefore, we find that at a general level the effect of IFRS presents a decrease on the cost of capital, especially Europe and Asia, but it must be considered as a short-term result. On the other hand, the findings in companies from Latin American countries show that there is no incidence on the indicator studied when changing the accounting standard, a phenomenon that can be generated by the time and recentness of its application. We conclude that there are factors that have not been considered in the measurements, such as the institutional infrastructure and the national culture, so it is recommended to select the sample according to similar characteristics and, additionally, control macroeconomic variables and unify criteria of the variables and financial indicators.